Assessing students' e-learning experiences in using learning managements systems - Chiang, Yan Chiou; Mohd Ayub, Ahmad Fauzi; Wong, Su Luan (Faculty of Educational Studies, Universiti Putra Malaysia, 2015)
With the flourishing advancement of ICT, it has changed our daily life in a lot of aspects including economic development, politic, social life, as well as education. The incorporation of ICT in education, especially the Internet changed the teaching and learning model. By using the Internet, e-learning was developed rapidly. This study explored the students’ e-learning experience in using Learning Management System (LMS). A total of 314 students from Universiti Putra Malaysia (UPM) were randomly selected from a stratified cluster sample. The research evaluated students’ e-learning experience using seven constructs which included quality of teaching, student interaction and engagement, clarify of goals and standard, quality of online resources, appropriate workload, student management and overall satisfaction with online experience. The finding showed that positive e-learning experience was identified in this study suggesting that the respondents had positive perception and were satisfied in using LMS.